Internal Migration Propensity Index (i-MPI) for Guatemala and Honduras: A tool to estimate the household-level likelihood of domestic migration - Ceballos, Francisco; Hernandez, Manuel A.; Hernandez, Alvaro Espinoza (CGIAR, 2023)
Worldwide, the large majority of migration occurs internally, with people relocating domestically within their country of origin. From a policy perspective, anticipating such migration decisions can be useful for targeting development programs and interventions, or as a monitoring tool, to capture the migration ‘sentiment’ among specific groups of interest. This paper describes the construction of an internal Migration Propensity Index (i-MPI) for Guatemala and Honduras, building on the existing MPI to predict external or cross-border migration available for these countries. The i-MPI aims to objectively measure and track the probability of individuals in a household of permanently migrating to a different location within their country, based on a small subset of household indicators and conditions that highly correlate with the (latent) decision to migrate domestically and, combined, best predict internal migration at the household level. The i-MPI avoids questions about migration intentions, which may be culturally sensitive, prone to misreporting, and difficult to monitor over time. Alternatively, it relies on a concise, reliable, and statistically-robust scoring index obtained from indirect indicators highly associated with migration decisions that are simple and easy to collect in the field. The paper describes the data and methodological approach to derive the index and presents the final i-MPI questionnaires, including a set of accompanying tools to implement it in the field.